Influence of Prebiotic Activity of Agave salmiana Fructans on Mucus Production and Morphology Changes in Colonic Epithelium Cell of Healthy Wistar Rats - Castillo Andrade, Amneris Iraida; García Chávez, Erika; Rivera Bautista, Cecilia; Oros Ovalle, Cuauhtemoc; Ruiz Cabrera, Miguel Angel; Grajales Lagunes, Alicia (Frontiers in Plant Science, 2021)
The beneficial health of evaluating prebiotic effect by the consumption of Agave salmiana fructans was assessmed in the epithelium of the cecum and proximal colon of Wistar rats fed at different doses for 35 days with regards to mucus production, morphological cell changes and the serum concentration of tumor necrosis factor-α (TNF-). Results showed a significant increase of mucus-secreting cells (P < 0.05), as well as a normal structure with preserved crypts, without morphological damage to colonic cells for a dose of 12.5% (w/w) with respect to the control and the other doses evaluated. The concentration of pro-inflammatory cytokine TNF-α was decreased significantly (p<0.05) in the groups with doses of 10 and 12.5% (w/w) at 7 and 35 days, respectively. This effect was positively correlated with the reduction of inflammation in epithelial cells. This study provides direct evidence of the effects of the Agave salmiana fructans on the colonic epithelium, demonstrating that a diet supplemented with 12.5% of fructans for 35 days exerts health benefits through the strengthening of the mucosa layer, which favors the adherence of the bacterial population and suppresses inflammation.